Sex Without Contraceptives in a Multicenter Study of Adolescent Emergency Department Patients. (22nd November 2019) - Chernick, Lauren S.; Chun, Thomas H.; Richards, Rachel; Bromberg, Julie R.; Ahmad, Fahd A.; McAninch, Brett; Mull, Colette; Shenoi, Rohit; Suffoletto, Brian; Casper, Charlie; Linakis, James; Spirito, Anthony; et al.
Abstract: Objectives: In the United States, rates of teenage pregnancy and sexually transmitted infections (STIs) remain exceptionally high, and racial and ethnic disparities persist. Emergency departments (EDs) care for over 19 million adolescents each year, the majority being minority and low socioeconomic status. Single‐center studies demonstrate infrequent use of contraceptives among adolescent ED patients and an association between risky sex and behaviors such as alcohol and drug use; however, no multicenter ED data exist. The objectives of this study were to 1) determine the prevalence of sex without contraceptives in a large multicenter adolescent ED study and 2) assess patient demographic and risky behaviors associated with sex without contraceptives. Methods: Participants aged 14 to 17 years ( n  = 3, 247) in 16 pediatric EDs across the United States completed an electronic survey. Questions focused on validated measures of risky sex; use of alcohol, tobacco, marijuana, and other drugs; and depression and violence. In this secondary analysis, we constructed univariable and multivariable models to identify demographic and behavioral factors associated with sex without contraceptives (our primary outcome), separately for adolescent males and females. Results: In the prior year, 17.4% (236/1, 356) of males and 15.8% (299/1, 891) of females had sex without contraceptives. In the multivariable model, sex without contraceptives for both genders was more likely among teens who were black, with conduct problems and participated in casual sex, binge drinking, or cannabis use. Sex without contraceptives was also more likely among Hispanic and cigarette‐smoking males, as well as depressed females. Conclusions: Adolescent ED patients across the United States are participating in risky sexual behaviors that increase their likelihood of pregnancy and STI acquisition. These adolescents report a number of problem behaviors, including substance use, which are strongly correlated with unprotected sex. The ED visit may be an opportunity to identify at‐risk adolescent patients, address risky behaviors, and intervene to improve adolescent health.